The Authenticity redefined: A new paradigm for sustainable heritage in yangon’s iconic governor's residence - Aung, Theingi (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: The Governor's Residence in Yangon, Myanmar, is a historical icon embodying the city's colonial past and architectural heritage. As urbanization and environmental challenges mount, redefining such heritage sites through sustainable practices becomes imperative. Methods: This study employed a qualitative research approach, integrating historical analysis, field observations, and stakeholder interviews. Data were gathered from archival records, peer-reviewed literature, and architectural site visits. Comparative analysis with similar heritage conservation projects in Southeast Asia provided additional insights. Findings: By employing eco-conscious architectural restoration, integrating renewable energy systems, and fostering community engagement, the residence can maintain its historical integrity while contributing to environmental stewardship. Additionally, adaptive reuse and educational initiatives can ensure its cultural and social relevance in the 21st century. Conclusion: The proposed approach underscores the importance of balancing historical preservation with sustainable modernization, offering a replicable framework for a heritage site. Novelty/Originality of the Study: This study introduces a novel approach to heritage conservation, combining eco-conscious restoration, renewable energy integration, and community engagement to transform a colonial-era structure into a sustainable cultural landmark. The findings present a replicable model for other historical sites facing similar urbanization and environmental challenges.